Primary parasitoid and hyperparasitoid guilds (hymenoptera) of grain aphid (Sitobion avenae F.) in northern Poland - Barczak Tadeusz; Dębek-Jankowska Amelia; Bennewicz Janina (Archives of Biological Sciences, 2015)
The aim of this study was to determine and compare the guilds of parasitic Hymenoptera associated with the grain aphid on rye and winter wheat in northern Poland. Of the seven species of primary parasitoids (Braconidae: Aphidiinae, Aphelinidae), parasitizing colonies of Sitobion avenae, the most numerous and most frequently occurring, included Praon volucre, Aphidius ervi and Aphidius uzbekistanicus. Primary parasitoids of grain aphids were largely eliminated by hyperparasitoids, mostly of the families Megaspilidae (Dendrocerus carpenteri), Figitidae-Alloxystini (Alloxysta spp. and Phaenoglyphis villosa) and Pteromalidae (Pachyneuron aphidis, Asaphes vulgaris, Coruna clavata), but D. carpenteri and Alloxysta spp. belonged to dominants and subdominants, respectively.